Study The Spin Down Luminosity And Flux Density For Pulsar Stars By Using Hallo Cone Model - Abdullah, Sundus A.; Sabah, Ban; Muder, Marwa (Iraqi Journal of Science, 2022)
There are different types of young isolated NSs: radio pulsars, compact central X-ray sources in supernova, magentas: anomalous x-ray pulsars (AXPs) and soft gamma-ray repeaters (SGRs).This paper shows that the value of magnetic field (B), characteristic age ( ), spin down luminosity ( equilibrium period ( and Flux density ( ) was determined depending on some properties of pulsar star, such as the value of period of the pulsar (P) and the time derivative period ( for sample stars which were adopted. The model that which adopted is Hallo Cone Model. The results showed that the Normal pulsar stars have a big magnetic field, equilibrium period and Spin down than the Millisecond pulsar stars.But Millisecond pulsar stars have large values of Luminosity and Flux density than Normal pulsar star that mean Normal pulsar star is lose its energy in long time that mean its younger than Millisecond Pulsar star.